2021
DOI: 10.3390/en14030570
|View full text |Cite
|
Sign up to set email alerts
|

Biogas Production from Anaerobic Co-Digestion of Spent Mushroom Substrate with Different Livestock Manure

Abstract: Spent mushroom substrate (SMS) is defined as the biomass waste generated during industrial mushroom cultivation. Utilization of SMS has been extensively researched and has immense potential as a sustainable substrate for generating biogas that can offset fossil fuel use. This closed loop energy generation process that can be set up in mushroom plants will reduce the dependence on fossil fuels and has the potential to reduce greenhouse gas emissions, which will benefit the environment. Anaerobic co-digestion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Large amounts of SMSs (approximately 5 kg) are generated during the production per kg of edible fungi ( Chang et al, 2020 ). According to statistics, the total yield of SMSs in China reached approximately 150 million tons each year ( Gao et al, 2021 ). Therefore, utilizing SMS resources scientifically and reasonably have become a critical issue.…”
Section: Introductionmentioning
confidence: 99%
“…Large amounts of SMSs (approximately 5 kg) are generated during the production per kg of edible fungi ( Chang et al, 2020 ). According to statistics, the total yield of SMSs in China reached approximately 150 million tons each year ( Gao et al, 2021 ). Therefore, utilizing SMS resources scientifically and reasonably have become a critical issue.…”
Section: Introductionmentioning
confidence: 99%
“…The co-substrates allow a better supply of nutrients and stability in biogas production. Gao et al [9] reported that the biogenic methane production increased by 414% when the spent mushroom substrate was co-digested with chicken manure. This is due to the improved carbon to nitrogen (C:N) ratios in the co-biomass, which helps to better degrade the microorganisms.…”
Section: Co-digestion Is a Well-established And Conventional Methods Where A Combination Of Different Feedstock Is Processed Into The Funmentioning
confidence: 99%
“…Hydrogen was used as carrier gas and the gas pressure was maintained at 0.38 Mpa. The injection volume was 500 μL [29].…”
Section: Ad Of Uhsmentioning
confidence: 99%